Progranulin promotes neurite outgrowth and neuronal differentiation by regulating GSK-3β - Gao, Xue (Protein Cell, 2010)
Progranulin (PGRN) has recently emerged as a key player in a subset of frontotemporal dementias (FTD). Numerous mutations in the progranulin gene have been identified in patients with familial or sporadic frontotemporal lobar degeneration (FTLD). In order to understand the molecular mechanisms by which PGRN deficiency leads to FTLD, we examined activity of PGRN in mouse cortical and hippocampal neurons and in human neuroblastoma SH-SY5Y cells. Treatment of mouse neurons with PGRN protein resulted in an increase in neurite outgrowth, supporting the role of PGRN as a neurotrophic factor. PGRN treatment stimulated phosphorylation of glycogen synthase kinase-3 beta (GSK-3β) in cultured neurons. Knockdown of PGRN in SH-SY5Y cells impaired retinoic acid induced differentiation and reduced the level of phosphorylated GSK-3β. PGRN knockdown cells were also more sensitized to staurosporine-induced apoptosis. These results reveal an important role of PGRN in neurite outgrowth and involvement of GSK-3β in mediating PGRN activity. Identification of GSK-3β activation as a downstream event for PGRN signaling provides a mechanistic explanation for PGRN activity in the nervous system. Our work also suggest that loss of axonal growth stimulation during neural injury repair or deficits in axonal repair may contribute to neuronal damage or axonal loss in FTLD associated with PGRN mutations. Finally, our study suggests that modulating GSK-3β or similar signaling events may provide therapeutic benefits for FTLD cases associated with PGRN mutations.